Transcription and Beyond: Delineating FOXG1 Function in Cortical Development and Disorders - Hou, Pei-Shan; hAilín, Darren Ó; Vogel, Tanja; Hanashima, Carina (Frontiers in Cellular Neuroscience, 2020)
FOXG1 is a member of the Forkhead family of genes with non-redundant roles in brain development, where alteration of this gene’s expression significantly affects the formation and function of the mammalian cerebral cortex. FOXG1 haploinsufficiency in humans is associated with prominent differences in brain size and impaired intellectual development noticeable in early childhood, while homozygous mutations are typically fatal. As such, FOXG1 has been implicated in a wide spectrum of congenital brain disorders, including the congenital variant of Rett syndrome, infantile spasms, microcephaly, autism spectrum disorder (ASD) and schizophrenia. Recent technological advances have yielded greater insight into phenotypic variations observed in FOXG1 syndrome, molecular mechanisms underlying pathogenesis of the disease, and multifaceted roles of FOXG1 expression. In this review, we explore the emerging mechanisms of FOXG1 in a range of transcriptional to posttranscriptional events in order to evolve our current view of how a single transcription factor governs the assembly of an elaborate cortical circuit responsible for higher cognitive functions and neurological disorders.